The determination of caesium and silver in soil and fungal fruiting bodies by electrothermal atomic absorption spectrometry - Anderson, Peter; Davidson, Christine M.; Littlejohn, David; Ure, Allan M.; Shand, Charles A.; Cheshire, Martin V. (Analytica chimica acta, 1996)
Methods have been developed for the determination of caesium and silver in soil and fungal samples by microwave-assisted aqua regia digestion, followed by electrothermal atomic absorption spectrometry. The procedure was found to be repeatable (for soil, RSD < 5%, n = 3, at caesium and silver concentrations of 1.8 and 0.6 mg g −1, respectively, and for fungi, RSD < 7%, n = 5, at caesium and silver levels of 20 and 1mg g −1, respectively) and reasonably efficient. Silver was recovered quantitatively from reference soils, but only about 80–85% of the caesium present could be extracted. Poorer caesium recoveries (< 70%) were obtained if, as part of the sample preparation procedure, solutions were taken to dryness in glass beakers prior to analysis. The detection limits were 0.02 mg Ag and 0.09 mg Cs per gram of dry soil, which are adequate for the determination of the analytes at typical environmental levels. The methods were applied in the analysis of three types of soil, a peaty podzol, a clay loam and a sandy loam and no significant matrix interferences were observed except in the determination of caesium in the sandy loam. For caesium, non-linear response curves, thought to be due to ionisation interference, were encountered using one atomic absorption spectrometer, but were not observed with the other instrument.